Evasione fiscale delle imprese - Federico Gabriele Etro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
– Theory of tax evasion is reviewed. The Marrelli approach is studied in a more general environment. Indirect tax evasion by firms is extended to the general case of oligopolic markets with a conjectural variations model and either a price discrimination model, considering both ad valorem and specific taxation. From the normative point of view, cut-off rules of tax enforcement are studied and modified inverse elasticity rules for optimal taxation are derived and shown to depend on the level of distortion on the supply side, i.e. on firms` collusion, shifting and tax evasion decisions.
Keywords: 330